Effectiveness and tolerability of lacosamide as add‐on therapy in patients with brain tumor–related epilepsy: Results from a prospective, noninterventional study in European clinical practice (VIBES). (24th April 2020) - Rudà, Roberta; Houillier, Caroline; Maschio, Marta; Reijneveld, Jaap C.; Hellot, Scarlett; De Backer, Marc; Chan, Jane; Joeres, Lars; Leunikava, Iryna; Glas, Martin; Grant, Robin
Abstract: Objective: To evaluate the effectiveness and tolerability of lacosamide added to one or two antiepileptic drugs (AEDs) in the treatment of patients with brain tumor–related epilepsy (BTRE), and to evaluate patients' global impression of change and quality of life (QoL). Methods: This was a prospective, multicenter, single‐arm, noninterventional study with a 6‐month observation period (EP0045; NCT02276053). Eligible patients (≥16 years old) had active BTRE secondary to low‐grade glioma (World Health Organization grade 1 and 2) and were receiving treatment with one or two AEDs at baseline. Lacosamide was initiated by the treating physician in the course of routine clinical practice. Primary outcomes were 50% responders (≥50% reduction in focal seizure frequency from baseline) and Patient's Global Impression of Change (PGIC) at month 6. Secondary outcomes included seizure‐free status and Clinical Global Impression of Change (CGIC) at month 6, change in QoL (5‐Level EuroQol‐5 Dimension Quality of Life Assessment) and symptom outcomes (MD Anderson Symptom Inventory–Brain Tumor) from baseline to month 6, and Kaplan‐Meier estimated 6‐month retention on lacosamide. Safety variables included adverse drug reactions (ADRs). Results: Patients were recruited from 24 sites in Europe. Ninety‐three patients received lacosamide (mean [standard deviation] age = 44.5 [14.7] years; 50 [53.8%] male; median baseline focal seizure frequency = five seizures/28 days [range = 1‐280]), of whom 79 (84.9%) completed the study. At 6 months, 66 of 86 (76.7%) patients were 50% responders and 30 of 86 (34.9%) were seizure‐free. Improvements on PGIC were reported by 49 of 76 (64.5%) patients. Based on CGIC, 52 of 81 (64.2%) patients improved. QoL and symptoms outcome measures remained stable. Kaplan‐Meier estimated 6‐month retention rate was 86.0% (N = 93). Fifteen (16.1%) patients reported ADRs; four (4.3%) had ADRs leading to discontinuation (N = 93). Significance: Results of this prospective, noninterventional study suggest that add‐on lacosamide is effective and generally well tolerated in patients with BTRE.